2018
DOI: 10.1177/1071100718768257
|View full text |Cite
|
Sign up to set email alerts
|

Resection of Medial Talocalcaneal Coalition With Interposition of a Pediculated Flap of Tibialis Posterior Tendon Sheath

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…18,29 Currently, there is no complete agreement concerning the best surgical strategy in children with RFF and TCC. Recommended treatments include bar resection alone or combined with tissue interposition and hindfoot correction, 12,15,18,23,32,44,47 isolated calcaneal osteotomy, 29 subtalar fusion or triple arthrodesis; the latter being recommended for subtalar OA, failure of previous surgeries, or large irresectable coalitions with severe heel valgus. 9,35 The known poor long-term outcomes of triple arthrodesis, however, make this an undesirable option, particularly for children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,29 Currently, there is no complete agreement concerning the best surgical strategy in children with RFF and TCC. Recommended treatments include bar resection alone or combined with tissue interposition and hindfoot correction, 12,15,18,23,32,44,47 isolated calcaneal osteotomy, 29 subtalar fusion or triple arthrodesis; the latter being recommended for subtalar OA, failure of previous surgeries, or large irresectable coalitions with severe heel valgus. 9,35 The known poor long-term outcomes of triple arthrodesis, however, make this an undesirable option, particularly for children.…”
Section: Discussionmentioning
confidence: 99%
“…9,35 More recently, some authors reported good results following bar resection, possibly associated with interposition of various tissues. 11,18,21,23,27,45,48 This treatment aims to relieve pain and increase subtalar motion.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, subtalar or triple arthrodesis has been recommended for pain relief [17,18]. More recently, some authors reported good results following bar resection, possibly associated with interposition of various tissues [8,[19][20][21][22][23][24]. This treatment aims to relieve pain and increase subtalar motion.…”
Section: Introductionmentioning
confidence: 99%
“…(17,18) More recently, some authors reported good results following bar resection, possibly associated with interposition of various tissues. (8,(19)(20)(21)(22)(23)(24) This treatment aims to relieve pain and increase subtalar motion.…”
Section: Introductionmentioning
confidence: 99%